2017
DOI: 10.1186/s12891-017-1533-1
|View full text |Cite
|
Sign up to set email alerts
|

Early surgery with antibiotics treatment had better clinical outcomes than antibiotics treatment alone in patients with pyogenic spondylodiscitis: a retrospective cohort study

Abstract: BackgroundPyogenic spondylodiscitis is a form of spinal infection that can result in severe back pain and even death. However, information is lacking on the relative effectiveness of various therapies. A retrospective chart review was conducted to investigate whether early surgical treatment of pyogenic spondylodiscitis coupled with intravenous antibiotics results in better patient prognoses than intravenous antibiotics therapy alone.MethodsAll patients treated for pyogenic spondylodiscitis at a single medical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
63
0
5

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(71 citation statements)
references
References 19 publications
3
63
0
5
Order By: Relevance
“…Tsai et al . report that early active debridement followed by treatment with antibiotics achieves better therapeutic results in cases of pyogenic spondylodiscitis.…”
Section: Introductionmentioning
confidence: 99%
“…Tsai et al . report that early active debridement followed by treatment with antibiotics achieves better therapeutic results in cases of pyogenic spondylodiscitis.…”
Section: Introductionmentioning
confidence: 99%
“…MRI is considered the modalityof choice for radiographic diagnosis, especially in severe lower back pain. Previous studies have reported an MRI sensitivity of 96%, a speci city of 93% and an accuracy of 94% in LPD, and MRI plays the key role in the continuous observation of LPD [24][25][26][27].…”
Section: Discussionmentioning
confidence: 99%
“…Biopsie während der operativen Therapie und ohne bis dahin begonnene Antibiotikagabe dar. In 83,7 % konnte so in der Arbeitsgruppe Tsai et al bei der intraoperativen Keimgewinnung ein Nachweis gelingen [7]. Die deutlich geringere Trefferwahrscheinlichkeit der CT-gesteuerten (perkutanen) Biopsie dokumentiert sich in der Arbeitsgruppe Ascione et al mit einem mikrobiologischen Erregernachweis von lediglich 22,2 % [4].…”
Section: Diagnostikunclassified
“…Unabhängig von der Art der Therapie und des Regimes werden gleichwohl immer folgende Ziele angestrebt: Relative OP-Indikation: ▪ Schmerzen ▪ geringgradige Destruktion/Deformität Tsai und Kollegen empfehlen in ihrer Arbeit ein frühzeitiges operatives Vorgehen auch bei Abwesenheit absoluter OP-Indikationen, also im Anfangsstadium einer Spondylodiszitis [7]. In der Vergleichsgruppe konservativ behandelter Patienten zeigte sich ein besseres Ergebnis hinsichtlich des Kyphosewinkels, der Dauer des Krankenhausaufenthaltes und der Dauer der Antibiotikagabe.…”
Section: Therapieunclassified
See 1 more Smart Citation